Evaluating the mechanism underlying antitumor effect of interleukin 27 on B cells of chronic lymphocytic leukemia patients. Issue 12 (7th May 2020) - Manouchehri‐Doulabi, Ehsan; Abbaspour, Somaye; Rostami, Shahrbano; Faranoush, Mohammad; Ghahramanfard, Farahnaz; Pak, Fatemeh; Barati, Mehdi; Kokhaei, Parviz; Momtazi‐Borojeni, Amir A.
Abstract: Chronic lymphocyte leukemia (CLL) is a B‐cell malignancy resisted to apoptosis. Recently, some studies indicated that cytokines such as interleukin 27 (IL‐27) can reduce B‐cell proliferation. The aim of this study is to evaluate the mechanism underlying the proapoptotic effect of IL‐27 on B cells of patients with CLL in comparison with B cells of normal subjects. The effect of IL‐27 on the antitumor activity of natural killer (NK) and T cells was also evaluated. Peripheral blood mononuclear cells (PBMCs) were isolated from 35 patients with CLL and 15 normal subjects. B cells and PBMCs were cocultured with IL‐27 and B cells apoptosis to evaluate proliferation. Both messenger RNA and protein expression of IL‐27 and IL‐27 receptor were determined using flow cytometry and real‐time polymerase chain reaction analysis. To evaluate the apoptotic effect of IL‐27 on B cells of patients with CLL, Annexin V‐FITC and 7‐AAD (BioLegend) fluorescent dyes were used. In addition, the IL‐27 effect on activation of T cell and NK cell was determined by determining CD96 molecule expression. IL‐27 and IL‐27 receptor expression in patients with CLL was significantly lower than that of normal subjects ( p  < .05). IL‐27 enhanced apoptosis of B cells in patients with CLL ( p  < .05) but this effect was not significantly observed in B cells of normal subjects ( p  > .05). Consequently, IL‐27 reduced the proliferation of B cells and enhanced NK cell activity ( p  < .05). IL‐27, through inducing apoptosis, can exert an inhibitory effect on cancer B cells of CLL patients with minimal effect on normal B cells.